Is There a Link Between Type 2 Diabetes Mellitus and Negative Symptoms in Schizophrenia? A Scoping Review - István Bitter; Pál Czobor; László Tombor (Brain Sciences)
Background/Objectives: Type 2 diabetes mellitus (T2DM) and impaired glucose metabolism are more prevalent among patients with schizophrenia than in the general population. The incidence of T2DM is associated with lifestyle factors that are often influenced by the negative symptoms of schizophrenia; comorbid T2DM may contribute to the reduced life expectancy observed in patients with schizophrenia. The existing literature reveals a scarcity of data regarding the potential causal relationship between T2DM and negative symptoms. Methods: A scoping review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria, utilizing the PubMed database to identify clinical studies investigating the association between T2DM and the negative (but not cognitive) symptom domain of schizophrenia. Subsequently, the reference lists of these identified publications were searched. Results: Seventeen publications were included. There is evidence supporting the association between impaired glucose tolerance and increased negative symptoms in patients with first-episode psychosis, and several studies indicate that poorer glucose metabolic status correlates with more severe negative symptoms. Patients with T2DM and chronic schizophrenia, however, had milder negative symptom scores compared to those without diabetes, although this association was less pronounced than in early disease stages. Conclusions: There is insufficient confirmatory evidence regarding the potential causality of T2DM on the negative symptoms of schizophrenia. Further, preferably prospective studies are needed to explore the complex and potentially causal relationship between T2DM and negative symptoms of schizophrenia. If T2DM were found to have a causal relationship with negative symptoms or to exacerbate pre-existing symptoms, it could lead to significant changes in therapeutic approaches for schizophrenia.